Relationship Between Functional Capacity and Health Related Quality of Life Among Cardiac Patients - Dhillon, Sawroop; Kaur Kang, Harmeet (National Journal of Community Medicine, 2023)
Background: Cardiac diseases make the patients prone for decline in their functional capacity and a diminished quality of life. The aim of the study is to assess relationship between functional capacity and Health Related Quality of Life (HRQOL) among cardiac patients. Methodology: This correlational research was carried out by examining cardiac patients who were receiving treatment at the selected hospital of Punjab, India. 6 Minute Walk Test (6MWT) and Quality of Life SF-36 were used to assess functional capacity and HRQOL among subjects. Results: Of the 196 cardiac patients, 80.1% patients were not able to cover more than 250 m of walking distance during 6MWT, depicting to have a low Functional capacity. Results also revealed that all (n=196) cardiac patients had poor quality of life. Furthermore, a significant mild positive correlation (.223) between the functional capacity and HRQOL was found among these cardiac patients. Conclusion: Functional capacity and quality of life are directly related to each other. Poor the functional capacity poor is the quality of life of cardiac patients. Thus, the results point towards the need for early involvement of patients in cardiac rehabilitation in order to improve health and prevent future complications.